Deconstruction Ahead: Examining the History and Potential of Highway Removal in Milwaukee - Florsheim, Morgan. (Tufts University. Tisch Library., 2024)
Thesis (M.A.)--Tufts University, 2024.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Penn Loh.; Committee: Kathryn Davies.; Keywords: Urban planning, Climate change, and Transportation.